1999
DOI: 10.1007/s002560050469
|View full text |Cite
|
Sign up to set email alerts
|

Spinal osteoblastoma: CT and MR imaging with pathological correlation

Abstract: The MRI appearances of spinal osteoblastomas are varied and show no characteristic features. MRI may also overestimate the extent of the lesion due to extensive reactive changes and adjacent soft tissue masses. CT should continue to be the investigation of choice for the characterisation and local staging of suspected spinal osteoblastomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 14 publications
2
69
0
1
Order By: Relevance
“…Since approximately one-third of the lesions are located in the spine, where they most often originate from the posterior vertebral elements, and radiographic features of tumors located in long and small bones can be unspecific, cross-sectional imaging is mandatory in characterization of the lesion and local staging in the majority of cases [1,4,6,15,16].…”
Section: Osteoblastomamentioning
confidence: 99%
“…Since approximately one-third of the lesions are located in the spine, where they most often originate from the posterior vertebral elements, and radiographic features of tumors located in long and small bones can be unspecific, cross-sectional imaging is mandatory in characterization of the lesion and local staging in the majority of cases [1,4,6,15,16].…”
Section: Osteoblastomamentioning
confidence: 99%
“…1 Pathological analysis of trauma, inflammation and tumour reveals woven bone or immature osteoid formation, which reflects the healing process of the lesion. Shaikh et al 18 observed low signal intensity reactive sclerosis in both T1WIs and T2WIs in osteoblastoma. Histopathological studies of reactive sclerosis show heavy mineralization of matrix associated with increased fibrovascular tissue within the marrow and perivascular infiltration of lymphocytes and plasma cells.…”
Section: End Plate Oedemamentioning
confidence: 99%
“…76 A variable enhancement pattern has been noted on MRI. 42,86 The reactive area surrounding the osteoblastoma often enhances on MRI, which may confound the interpreted boundaries of the lesion.…”
Section: Radiographic Presentation and Locationmentioning
confidence: 99%